Storage Policies and Maintenance Support Strategies in Warehousing Systems - Guo, Xiaolong (Springer Theses, Recognizing Outstanding Ph.D. Research, 2016)
This book studies storage policies in warehousing systems and maintenance-support strategies for critical operational systems in warehouses, which are the most important issues affecting operational efficiency of warehousing systems. It expands on the theory of class-based storage by considering a finite number of items in store, and also introduces the maintenance-support strategy founded on performance-based contract theory. It is a valuable resource for researchers, practitioners and engineers in the fields of industrial engineering, operations management, operations research and management science.